Test of innovative silicon detectors for the monitoring of a therapeutic proton beam. (October 2020) - Sacchi, R; Ahmadi Ganjeh, Z; Arcidiacono, R; Attili, A; Cartiglia, N; Donetti, M; Fausti, F; Ferrero, M; Giordanengo, S; Hammad Ali, O; Mandurrino, M; Manganaro, L; et al.
Abstract: Beam monitoring in particle therapy is a critical task that, because of the high flux and the time structure of the beam, can be challenging for the instrumentation. Recent developments in thin silicon detectors with moderate internal gain, optimized for timing applications (Ultra Fast Silicon Detectors, UFSD), offer a favourable technological option to conventional ionization chambers. Thanks to their fast collection time and good signal-to-noise ratio, properly segmented sensors allow discriminating and counting single protons up to the high fluxes of a therapeutic beam, while the excellent time resolution can be exploited for measuring the proton beam energy using time-of-flight techniques. We report here the results of the first tests performed with UFSD detector pads on a therapeutic beam. It is found that the signal of protons can be easily discriminated from the noise, and that the very good time resolution is confirmed. However, a careful design is necessary to limit large pile-up inefficiencies and early performance degradation due to radiation damage.